Ephedramine therapeutic effectiveness for allergic rhinitis treatment: a double blind placebo controlled trial - Mohamad Ali, Abdulghani; Al turaihy, Safa; Ahmad Salih, Anas; Abd Al Sawah, Deyab (Tikrit Journal of Pharmaceutical Sciences, 2023)
Background : Allergic rhinitis is a common allergic disease worldwide. To date therewas no curable treatment. Study design: Double blind placebo controlled clinicaltrial. Patients and Methods: Ephedramine was evaluated as treatment for allergicrhinitis. One hundred and twenty subjects were included in the study. The patientswas divided into two groups (A) and (B), given either placebo or ephedramine(acombination of pseudoephedrine HCl 60mg plus chlorpheneramine maleate 2.5mg). The drug was given twice daily for subsequent four weeks. Patients withallergic rhinitis and associated conditions were involved in the study. Results: Ourpatients demonstrate a very well response to ephedramine; 44.8% had completeremission from congestion at the end of trial while 78.8% had remission fromRhinorrhoea, 71.1% remitted from sneezing and 80.4% had complete remission frompruritus. The corresponding values in placebo group were 31.5%, 31.5%, 17.8% and31.4% respectively. Side effects of ephedramine include headache (32.7%), dizziness(27.7%), and dry mouth (21.8%). The same above side effects were reported inplacebo group, but with lower frequency. Conclusion: Ephedramine was effective astreatment for allergic rhinitis and associated conditions with non significant sideeffects and minimized antihistamine effect of chlorpheneramine maleate by -adrenergic effect of pseudoephedrine.